Exploring the satisfaction of surgical patients in the Surgical ER short-stay unit. Correlation of the initial anxiety and pain with the final satisfaction: a quality criterion of nursing - charisi, Evangeli; Tagarakis, Georgios; Zacharoulis, Dimitrios; Tsilimingas, Nikolaos (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Introduction: The main indicator for the evaluation of nursing services is the overall perception of the patients receiving care from the health care unit they visit. Purpose: Was To investigate the satisfaction of surgical patients hospitalized in SSU-ER-short stay unit (MVN). In addition, to investigate the correlation between the initial anxiety and pain and the severity of final diagnosis. Materials and methods: The study included a total of 302 consecutive patients hospitalized in the MVN during a period of six months. The satisfaction questionnaire used were the SERVQUAL.I and the "Hospital Anxiety and Depression Scale (Hospital Anxiety and Depression Scale, HADS). The pain assessment was done by the visual analog scale (VAS). Results: The study included 198 men aged 49,3 ± 25,39 years and 104 women aged 56,78 ± 20,58 years. The average patient satisfaction was equal to or higher than 6 in the 7-point Likert scale (all dimensions contemplated). The average stress (7,67 ± 2,90) was higher than the threshold 7 for normal price, while in the case of depression the average findings were within normal limits (5,00 ± 2,98). Statistically significant differences were observed in the level of overall satisfaction among the various categories of patients [F (5,296) = 4,130, p = 0,001)]. Higher levels of anxiety and pain were positively associated with overall satisfaction (p <0,01). Conclusion: The level of satisfaction in MVN is important, but requires individualized care and improvement of objective parameters associated with organizational and economic factors.